Prejudices on In-vitro Fertilization: Experiences from Couples Struggling with Fertility of Urban Dhaka - Habib, Sumiaya (Social Science Review, 2023)
The biomedical treatment of infertility has spread throughout the world rapidly, though the cultural understanding of its techniques stagger in various cultures and societies. The local moral ideologies and cultural urge of fertility have treated the infertile people miserably. In Bangladesh, biomedical treatments of infertility are being introduced, and many are approaching it, depending upon not only their affordability but also on various socio-cultural factors. The cultural interpretation of in-vitro fertilization (IVF) depends on various social components, like patriarchy, moral values, and belief system related to childbirth. Thus, the social exposure and moral pioneers of the recipient of treatment play significant roles in postulating the conception of IVF. This paper identifies the cultural interpretation of IVF among the infertile couples of urban Dhaka through their experience in addressing biomedical infertility treatment. Social Science Review, Vol. 40(1), Jun 2023 Page 41-55